(untitled) (Research, Society and Development, 2021)
Objective: To verify the psychological impacts of COVID-19 on health professionals. Methodology: This is an exploratory, descriptive research with a quantitative approach. The study was carried out in a private higher education institution, located in the city of Vitoria da Conquista, Southwest of Bahia. The instruments used for data collection were a sociodemographic questionnaire developed by the study researchers, DASS-21 (Depression Anxiety Stress) questionnaire developed by Lovibond and Lovibond (1995), and finally the Pittsburgh Sleep Quality Index questionnaire was applied. (PSQI) developed by Buysse. Results: Twelve health professionals participated in this research, among the data collected from the participants, regarding the level of Anxiety, Depression and Stress, 83.3% of respondents had the index within normality, the PSQI, based on the scores found in the sample, 58.3% of respondents had poor sleep quality. Conclusion: it is concluded that the levels of anxiety, depression and stress among health professionals were considered predominantly normal and the frequency of poor sleep quality in this study was high.